2008
DOI: 10.1111/j.1399-0004.2008.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin T mutation in familial cardiomyopathy with variable remodeling and restrictive physiology

Abstract: We identified a unique family with autosomal dominant heart disease variably expressed as restrictive cardiomyopathy (RCM), hypertrophic cardiomyopathy (HCM), and dilated cardiomyopathy (DCM), and sought to identify the molecular defect that triggered divergent remodeling pathways. Polymorphic DNA markers for nine sarcomeric genes for DCM and/or HCM were tested for segregation with disease. Linkage to eight genes was excluded, but a cardiac troponin T (TNNT2) marker cosegregated with the disease phenotype. Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 36 publications
3
57
0
1
Order By: Relevance
“…4 Studies evaluating specific correlations between genotype and clinical outcomes have reported conflicting findings. 1,2,[5][6][7][8][9][10][11] In a cohort of 203 patients, Olivotto et al 12 showed that adverse combined outcomes (cardiovascular death, nonfatal stroke, or progression to advanced heart failure symptoms) occurred more frequently in patients who tested positive for a pathogenic sarcomere mutation compared with those without pathogenic mutations. Although important, this study was limited by the small number of patients and the use of combined morbidity and mortality end points.…”
mentioning
confidence: 99%
“…4 Studies evaluating specific correlations between genotype and clinical outcomes have reported conflicting findings. 1,2,[5][6][7][8][9][10][11] In a cohort of 203 patients, Olivotto et al 12 showed that adverse combined outcomes (cardiovascular death, nonfatal stroke, or progression to advanced heart failure symptoms) occurred more frequently in patients who tested positive for a pathogenic sarcomere mutation compared with those without pathogenic mutations. Although important, this study was limited by the small number of patients and the use of combined morbidity and mortality end points.…”
mentioning
confidence: 99%
“…Differential effects of mutations on sarcomeric properties such as myofilament sliding, Ca 2ϩ sensitivity, or ATPase activity have emerged as a mechanism underlying those phenotypes (8,9). Recent studies have shown that RCM is part of the spectrum of sarcomeric gene mutations, including pediatric RCM (7,(35)(36)(37)(38)(39)(40). In the largest series of pediatric RCM reported to date, mutation screening of eight sarcomeric genes and desmin suggested a predominant role of mutations in TNNI3, TNNT2, and ACTC in disease pathogenesis (7).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in TNNT2 can also cause HCM as well as restrictive cardiomyopathy (RCM) and non-compaction cardiomyopathy (NCCM). [28][29][30] Non-compaction cardiomyopathy caused by a TNNT2 mutation was only reported once in the literature and was also identified in person III-1 from family D ( figure 2). 30 Until recently, NCCM was believed to be a rare form of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%